The Rating Assesment of Russian Regions by the Level of Tourism Development. Analysis of the Position of the Kemerovo Region - ZAYTSEVA, Anna; BREL, Olga; KAIZER, Philipp (Journal of Environmental Management and Tourism, 2019)
The most important task of strategic development planning is adequate assessment of the socio-economic status of the regions, as well as identifying the causes of the lag in the development of some of them. Recently, various types of ratings have become popular tool for conducting such an assessment. Ratings allow countries and regions to realize their position and their role in the development of tourism, to assess their competitive advantages that increase the tourist attractiveness of the territory. The article discusses the problem of the place of the Kemerovo region in the rating of the tourist attractiveness of Russian regions. The authors demonstrate the change in the indicators characterizing the state of the tourist sector of the Kemerovo region over the past 4 years and discuss the possibilities of its changing for the better.